2013
DOI: 10.1093/cid/cis1029
|View full text |Cite
|
Sign up to set email alerts
|

Pro-adrenomedullin as a Novel Biomarker for Predicting Infections and Response to Antimicrobials in Febrile Patients With Hematologic Malignancies

Abstract: ProADM and PCT have promising roles in assisting clinicians in managing febrile HM patients. However, proADM appears to have the advantage of predicting localized bacterial infection and differentiating sepsis from SIRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
36
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 40 publications
9
36
1
Order By: Relevance
“…The values of MR-proADM in this subgroup are similar to the global group. These results are similar to several studies in patients with hematological and solid cancer (57)(58)(59). In an extensive study of hematological patients, Al Shuaibi et al (57) demonstrated the value of initial MR-proADM levels of septic patients and nonseptic patients with SIRS; however, PCT levels were not useful in this sense.…”
Section: Marker Clearancesupporting
confidence: 85%
“…The values of MR-proADM in this subgroup are similar to the global group. These results are similar to several studies in patients with hematological and solid cancer (57)(58)(59). In an extensive study of hematological patients, Al Shuaibi et al (57) demonstrated the value of initial MR-proADM levels of septic patients and nonseptic patients with SIRS; however, PCT levels were not useful in this sense.…”
Section: Marker Clearancesupporting
confidence: 85%
“…PCT was a useful marker for diagnosing systemic or severe bacterial infections whereas it was hardly increased in local or mild systemic bacterial infection [17,18]. Pneumonia is recognized as severe LRTI closer to systemic infection whereas the symptoms of bronchitis are relatively milder.…”
Section: Discussionmentioning
confidence: 99%
“…No independent associations were found between MR-proADM and newonset albuminuria. This is the first study evaluating the relationship between MR-proADM and mortality in patients with type 2 diabetes and the first to evaluate the relationship with newonset albuminuria (13,16,19,20,(24)(25)(26)31).…”
Section: Discussionmentioning
confidence: 99%
“…Increased plasma MR-proADM levels are also associated with the development of CV morbidity and have a role in predicting adverse outcomes in patients with coronary artery disease (14,16) and heart failure (15,17) and patients presenting to the emergency department with dyspnea (18). MR-proADM may also be useful for excluding the diagnosis of left ventricular failure (19), predicting the response to antimicrobials and estimating prognosis in patients with sepsis (20,21). Few studies exist with long-term follow-up (22).…”
mentioning
confidence: 99%